2011
DOI: 10.1002/maco.201106075
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of inhibitors with corrosion scale formed on N80 steel in CO2‐saturated NaCl solution

Abstract: The performance of the selected inhibitors, including thioglycolic acid (TGA), diethylenetriamine (DETA), and naphthene acid imidazolines (IM), on the bare surface of N80 steel and its scaled surface pre-corroded in CO 2 -saturated 1%NaCl solution was investigated by weight-loss method, electrochemical measurements using rotating cylinder electrode and surface analytical methods (SEM, XRD, and EPMA). The results indicate that there is a remarkable difference in inhibition efficiency of inhibitors on the N80 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…1-Bromotetradecane, hydroxylamine hydrochloride, triethylamine, silica gel 100, and paraformaldehyde (Fluka Chemie AG) and 1-tetradecene were used as received. Safrole (1) and eugenol (2) were purchased from Aldrich Co.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Bromotetradecane, hydroxylamine hydrochloride, triethylamine, silica gel 100, and paraformaldehyde (Fluka Chemie AG) and 1-tetradecene were used as received. Safrole (1) and eugenol (2) were purchased from Aldrich Co.…”
Section: Methodsmentioning
confidence: 99%
“…The white solid was crystallized from pet-ether to give the ditetradecylhydroxylamine 5 (3.5 g, 22.8%). The ltrate ($700 cm 3 ) was concentrated and the residual solid was crystallized from petroleum ether to give the white crystal of the tetradecylhydroxylamine 4 (9.5 g, 57.5% [1,3]dioxol-5-ylmethyl)-2tetradecylisoxazolidine (7). A mixture of hydroxylamine 4 (1.50, 6.5 mmol), paraformaldehyde (0.36 g, 12 mmol), and safrol (alkene) 1 (1.95 g, 12 mmol) in toluene (6 mL) was stirred using a magnetic stir bar at 110 C in an RB ask at 110 C under N 2 for 7 h. Aer removal of solvent, the residual mixture was chromatographed over silica gel using 5 : 1 hexane/ether as eluant to give adduct 7 as a white solid (2.2 g, 84%).…”
Section: N-tetradecylhdroxylaminementioning
confidence: 99%
“…Two peaks in C 1s spectra (Figure 5b) at 284.8 and 289.4 eV correspond to the adsorbed hydrocarbons and amorphous FeCO 3 , respectively. [27,28] The peaks in the Fe 2p spectra at 711.4 and 724.3 eV correspond to FeCO 3 , and the peak with a binding energy of 717.4 eV is associated with Fe 2 O 3 , [4,29] which originates from the oxidation of Fe 2+ after the specimens are taken out from the autoclave. By combining the XRD results, XPS patterns as well as results of previous literature, [6,30,31] it could be confirmed that both amorphous/crystalline FeCO 3 form at this condition and the matrix-like site is mainly amorphous FeCO 3 to a great degree.…”
Section: Potentiodynamic Polarization Testsmentioning
confidence: 99%
“…[3] Field evidence indicated that CO 2 -induced sweet corrosion has caused more than 60% failures in equipment and facility with the attendant capital and operating expenditures. [4,5] Sodium bicarbonate (NaHCO 3 ) is served as a pH stabilizer proceeding to flow into the pipelines, where its concentration varies from small quantities to high levels, and its purpose is to restrict the general corrosion of pipelines within an acceptable range. [6,7] Several studies have focused on the role of bicarbonate ion (HCO 3 − ) in the corrosion of carbon steel exposed to CO 2 aqueous media [8][9][10][11][12][13][14] and provided an important contribution to the understanding of the corrosion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…3-amino-1, 2, 4, triazole was used as corrosion inhibitor for API X52 pipeline steel in CO 2 saturated brine solution using RCE [99]. Others [100], have evaluated thioglycolic acid (TGA), diethylenetriamine (DETA), and naphthene acid imidazolines as corrosion inhibitors of precorroded N80 steel in CO 2 -saturated 1% wt. NaCl solution using an RCE.…”
Section: Corrosion Inhibitorsmentioning
confidence: 99%